Improving Greywater Quality by Aeration and Membrane Filtration - Anwar, Faisal; Gardner, E.; Sarker, D.I.P.O.K.C.H.A.N.D.R.A. (King Saud University, Riyadh, Saudi Arabia, 2016)
Water conservation is an important issue in most arid and semi-arid regions and the reuse of treated wastewater is becoming popular in many countries. Greywater is the wastewater from household showers, baths, sinks and washing machines which can potentially be recycled for domestic irrigation and therefore reduce household demand for potable water. In this paper, the improvement of greywater quality was investigated using aeration and membrane filtration process. The raw greywater was collected in two batches from a home washing machine and kept untreated for 12, 24, 36, and 48hrs before aeration. The aeration experiment was run continuously for 7 days and different water quality parameters such as dissolved oxygen (DO), dissolved organic carbon (DOC), pH and nitrogen species (NH3-N, NO2-N and NOx-N) were measured. The results of aeration revealed that DO levels could be increased to 9 mg/L which is good for aquatic water quality. The DOC level was decreased up to 62% in 80hrs of aeration whereas NH3-N was reduced by 85% in 30hrs of aeration. However, pH level was maintained between 8-8.5. The aerated greywater was further treated using membrane filtration (MF) and the results showed that DOC level was further reduced by 44% and the total coliform (TC) was reduced to 9 cfu/100mL. The significant reduction of DOC and TC indicates that the MF can be used effectively to reduce the overall pathogen concentration in greywater. Comparing the results of treated and untreated greywater revealed that the aeration followed by MF can be considered as an effective method to improve overall greywater quality for irrigation.